Variants in PPP2R2B and IGF2BP3 are associated with higher tau deposition. Issue 1 (26th September 2020) - Ramanan, Vijay K; Wang, Xuewei; Przybelski, Scott A; Raghavan, Sheelakumari; Heckman, Michael G; Batzler, Anthony; Kosel, Matthew L; Hohman, Timothy J; Knopman, David S; Graff-Radford, Jonathan; Lowe, Val J; Mielke, Michelle M; et al.
Abstract: Tau deposition is a key biological feature of Alzheimer's disease that is closely related to cognitive impairment. However, it remains poorly understood why certain individuals may be more susceptible to tau deposition while others are more resistant. The recent availability of in vivo assessment of tau burden through PET provides an opportunity to test the hypothesis that common genetic variants may influence tau deposition. We performed a genome-wide association study (GWAS) of tau-PET on a sample of 754 individuals over age 50 (mean age 72.4 years, 54.6% men, 87.6% cognitively unimpaired) from the population-based Mayo Clinic Study of Aging. Linear regression was performed to test SNP associations with AV-1451 ( 18 F-flortaucipir) tau-PET burden in an Alzheimer's-signature composite region of interest, using an additive genetic model and covarying for age, sex, and genetic principal components. Genome-wide significant associations with higher tau were identified for rs76752255 ( p =9.91 x 10 −9, β = 0.20) in the tau phosphorylation regulatory gene PPP2R2B (protein phosphatase 2 regulatory subunit B) and for rs117402302 ( p =4.00 x 10 −8, β = 0.19) near IGF2BP3 (insulin-like growth factor 2 mRNA binding protein 3). The PPP2R2B association remained genome-wide significant after additionally covarying for global amyloid burden and cerebrovascular disease risk, while the IGF2BP3 association was partially attenuated after accounting for amyloid load. In addition to these discoveries, three SNPs within MAPT (microtubule-associated protein tau) displayed nominal associations with tau-PET burden, and the association of the APOE (apolipoprotein E) ɛ4 allele with tau-PET was marginally nonsignificant ( p =0.06, β = 0.07). No associations with tau-PET burden were identified for other SNPs associated with Alzheimer's disease clinical diagnosis in prior large case-control studies. Our findings nominate PPP2R2B and IGF2BP3 as novel potential influences on tau pathology which warrant further functional characterization. Our data is also supportive of previous literature on the associations of MAPT genetic variation with tau, and more broadly supports the inference that tau accumulation may have a genetic architecture distinct from known Alzheimer's susceptibility genes, which may have implications for improved risk stratification and therapeutic targeting. Graphical Abstract: